Statin use and risk of acute diverticulitis: A population-based case-control study. Issue 20 (15th May 2020) - O'Grady, Michael; Clarke, Louise; Turner, Gregory; Doogue, Matt; Purcell, Rachel; Pearson, John; Frizelle, Frank
Abstract : Abstract: The goal of the study was to examine the association between statin use and the development of acute diverticulitis requiring hospital admission. Acute diverticulitis is a common and costly gastrointestinal disorder. Although the incidence is increasing its pathophysiology and modifiable risk factors are incompletely understood. Statins affect the inflammatory response and represent a potential risk reducing agent. A retrospective, population-based, case-control study was carried out on a cohort of adults, resident in Canterbury, New Zealand. All identified cases were admitted to hospital and had computed tomography confirmed diverticulitis. The positive control group comprised patients on non-aspirin nonsteroidal anti-inflammatory drugs (NSAIDs), and the negative control group were patients on selective serotonin reuptake inhibitors (SSRIs). Medicine exposure was obtained from the Pharmaceutical Management Agency of New Zealand. Subgroup analysis was done by age and for complicated and recurrent diverticulitis. During the study period, there were 381, 792 adults resident in Canterbury. The annual incidence of diverticulitis requiring hospital presentation was 18.6 per 100, 000 per year. Complicated disease was seen in 37.4% (158) of patients, and 14.7% (62) had recurrent disease. Statins were not found to affect the risk of developing acute diverticulitis, nor the risk of complicated or recurrent diverticulitis. Subgroup analysis suggested statin use was associated with a decreased risk of acute diverticulitis in the elderly (age >64 years). NSAIDs were associated with a decreased risk of acute diverticulitis (risk ratio = 0.65, confidence interval: 0.26–0.46, P  < .01), as were SSRIs (risk ratio = 0.37, confidence interval: 0.26–0.54, P  < .01). This population-based study does not support the hypothesis that statins have a preventative effect on the development of diverticulitis, including complicated disease. We also found a decreased risk of diverticulitis associated with NSAID and SSRI use.